Influence of pre-pregnancy leisure time physical activity on gestational and postpartum weight gain and birth weight – a cohort study. (18th August 2017) - Hegaard, Hanne Kristine; Rode, Line; Katballe, Malene Kjær; Langberg, Henning; Ottesen, Bent; Damm, Peter
Abstract: In order to examine the association between pre-pregnancy leisure time physical activities and gestational weight gain, postpartum weight gain and birth weight, we analysed prospectively collected data from 1827 women with singleton term pregnancies. Women were categorised in groups of sedentary women, light exercisers, moderate exercisers and competitive athletes. The results showed that sedentary women on average gained 14.1 kg during pregnancy, whereas light exercisers gained 13.7 kg, moderate exercisers gained 14.3 kg and competitive athletes 16.1 kg. Competitive athletes had an increased risk of having a gestational weight gain above Institute of Medicine (IOM) recommendations with an odds ratio of 2.60 (1.32–5.15) compared to light exercisers. However, birth weight and one year postpartum weight was similar for all four groups. Thus, although competitive athletes gain more weight than recommended during pregnancy, this may not affect birth weight or postpartum weight. Impact statement: What is already known on this subjectPrevious studies have found that increased pre-pregnancy physical activity is associated with lower gestational weight gain during the last trimester, but showed no association between the pre-pregnancy level of physical activity and mean birth weight. What the results of this study addWe found that women classified as competitive exercisers had a 2.6-fold increased risk of gaining more weight than recommended compared to light exercisers. Nearly 6 out of 10 women among the competitive exercisers gained more weight than recommended by IOM. Surprisingly, this did not appear to increase birth weight or post-partum weight gain, but other adverse effects cannot be excluded. What the implications are of these findings for clinical practice and/or further researchIn the clinical practice it may be relevant to focus on and advise pre-pregnancy competitive exercisers in order to prevent excessive gestational weight gain.